Exploring phenomenological in relationship marketing practices of Sarawak women entrepreneurs / Carolina Sandra Giang, Gluma Saban and Corina Joseph. - Giang, Carolina Sandra; Saban, Gluma; Joseph, Corina (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2016)
Building and maintaining a long-term relationship with others are an important aspect of women entrepreneurs in operating their businesses. The interpersonal relationship has been acknowledged as the main factor to define relationship marketing. Despite the recognition of the interpersonal relationship as an important skill, there are still limited exploratory qualitative studies to comprehend and help understand the nature of the interpersonal relationship of women entrepreneurs within the context of relationship marketing. Therefore, the purpose of this paper is to understand the meaning and practices of relationship marketing concept by women entrepreneurs within the context of relationship marketing. This study adopts qualitative phenomenological method using in-depth interviews to extract and identify the relationship marketing common practices of the lived interpersonal relationships experiences of 10 women entrepreneurs from Kuching, Sarawak, Malaysia. The study follows Creswell's (2013) data analysis and representation for phenomenological approach and generate five emergent themes: 1) Social Bonding Leading to Long-term Friendship; 2) Coalition with Rivals; 3) Empathetic Towards Customers' Needs; 4) Uprightness is Key to Good Reputation and Image; and 5) Network of Relationship. While the finding may not be generalised to other studies and therefore becomes the limitation of this study. Nevertheless, the findings may encourage researchers to look beyond the studies of personal traits and characteristics of women entrepreneurs.